Complete genome sequence of the symbiotic strain Bradyrhizobium icense LMTR 13T, isolated from lima bean (Phaseolus lunatus) in Peru - Ormeño-Orrillo E. (2018)
The complete genome sequence of Bradyrhizobium icense LMTR 13T, a root nodule bacterium isolated from the legume Phaseolus lunatus, is reported here. The genome consists of a circular 8,322,773-bp chromosome which codes for a large and novel symbiotic island as well as genes putatively involved in soil and root colonization. © 2018 Ormeño-Orrillo et al.